Impact of the equation of state on calculated adsorption isotherm using DFT. (2nd November 2017) - Butz, Julian; Zimmermann, Patrick; Enders, Sabine
Highlights: The used EOS within the DFT has an impact on the predicted capillary condensation. The density profile in the pore depends on the selected EOS. The predicted adsorption isotherms depend only slightly on the used EOS. Abstract: In the early state of process development, usually high quality experimental data are often missing, especially, if the experimental effort is quite large. This situation occurs for the separation of very similar components, which must be separated applying adsorption. In principle, adsorption isotherms can be predicted using the density functional approach in combination with a suitable thermodynamic model in order to describe the fluid properties. In this paper, we study the adsorption of propanal, where no experimental data for comparison are available for verification of the modelling results. Therefore, we use three different equations of state (EOS), namely the Peng-Robinson and two versions out of the SAFT framework. The two versions are the Perturbed Chain – Statistical Association Fluid Theory (PC-SAFT) and the Perturbed Chain Polar – Statistical Association Fluid Theory (PCP-SAFT) including an additional dipole contribution. Although both SAFT versions are superior in modelling the phase behavior, especially the saturated liquid volume, the predicted adsorption isotherms were close together. However, the calculated condensation pressure in the pore depends on the chosen EOS. All equations of state lead to similar surface tensions, if they are coupled with the density gradient theory. The calculated surface tensions using one of the two SAFT versions are in excellent agreement with experimental data taken from the literature.